Flora of the State of Paraíba, Brazil: Loranthaceae Juss. (Acta Scientiarum. Biological Sciences, 2015)
The family Loranthaceae Juss., characterized by its parasitic habit, is rarely studied in Brazil. Current research provides a taxonomic survey of Loranthaceae in the State of Paraiba, northeastern Brazil, in which ten species belonging to four genera have been recorded: Passovia (one species), Psittacanthus (two species), Pusillanthus (one species) and Struthanthus (six species). Struthanthus concinnus Mart. was found for the first time in the state of Paraíba. A key to the species identification and taxonomic descriptions is presented, with images, geographic distribution and host data.